Analisis Kelayakan Usaha Ebi (Studi Kasus: Desa Arung Medang Kecamatan Tangaran) - Merdekawati, Dewi; Kurniawan, Deden; Istiqamah, Nur; Harmoko (Nekton, 2021)
Sea potential is very abundant in the village of Arung Medang. One of them is shrimp which is processed into dried shrimp, but only a small part of the community who become dried shrimp entrepreneurs, and it makes the production is fairly low. This study aims to analyze the feasibility of dried shrimp entrepreneurs with a case study in Arung Medang village, Tangaran sub-district. The samples in this study were five people with the sampling conducted by using the purposive sampling technique. The research method used is a financial analysis by calculating costs, revenues, opinions, business feasibility or R/C Ratio, Break Even Point, Payback Period. The results of this study indicate that: the total cost in this study was Rp.2.759.000, the revenue for was Rp.5.300.000, the net income was Rp.2.541.000, the break even point was Rp.26,3 kilograms, the break even point price was Rp.280.191, the payback period 0,054 or 20 working days, the capital will be returned. Where the feasibility level of the dried shrimp business was 1.9, it means that the dried shrimp entrepreneurs are Financially feasible to run because of the R/C Ratio <1.